Distributed adaptive switching control of uncertain switched affine multi-agent systems. (November 2020) - Sinafar, Behzad; Kharrati, Hamed; Badamchizadeh, Mohammad Ali; Baradarannia, Mahdi
Abstract: In this paper, motivated by the need for distributed control of multi-agent networks consist of switched affine systems, a distributed leader following consensus controller is developed. Different from most existing methods with affine control multi-agent systems, switched affine multi-agent systems face additional difficulties in the analysis and control, meanwhile affine diffusive coupling consensus algorithms are not applicable. So, in this paper switching signal is considered as the only control mechanism. Two consensus algorithms are proposed based on min-switching control and a new distributed embedded pulse width modulation (PWM) technique, in which local and neighbors output feedback are used to construct control input via an adaptive observer. Proposed observer-based distributed adaptive switching strategies guarantee stability of the overall network in the presence of uncertain affine term. Finally, proposed distributed control algorithms are verified by simulation of a switched affine multi-agent system.